The search for the number form area: A functional neuroimaging meta-analysis. (July 2017) - Yeo, Darren J.; Wilkey, Eric D.; Price, Gavin R.
Highlights: Recent studies suggest the existence of a putative NFA in the ITG. Signal dropout was suggested to underlie prior null findings that used fMRI. Our meta-analyses suggest an NFA in the right ITG if it is truly functionally specific. Task demands, instead of signal dropout might account for null fMRI findings. The right ITG and a frontoparietal network comprise a 'symbolic number network'. Abstract: Recent studies report a putative "number form area" (NFA) in the inferior temporal gyrus (ITG) suggested to be specialized for Arabic numeral processing. However, a number of earlier studies report no such NFA. The reasons for such discrepancies across studies are unclear. To examine evidence for a convergent NFA across studies, we conducted two activation likelihood estimation meta-analyses on 31 and a subset of 20 neuroimaging studies that have contrasted digits with other meaningful symbols. Results suggest the potential existence of an NFA in the right ITG, in addition to a 'symbolic number processing network' comprising bilateral parietal regions, and right-lateralized superior and inferior frontal regions. Critically, convergent localization for the NFA was only evident when contrasts were appropriately controlled for task demands, and does not appear to depend on employing methods designed to overcome fMRI signal dropout in the ITG. Importantly, only five studies had foci within the identified ITG NFA cluster boundary, indicating that more empirical evidence is necessary to determine the true functional specialization and regional specificity of the putative NFA.